DETERMINANTS OF FINANCIAL PERFORMANCE IN THE INDONESIAN BANKING SECTOR - Zusma Widawaty A Wahab; Miftahul Jannah; Nurul Mawaddah; Desy Puspita; Anggraeni Yunita (AIBPM Publisher, 2026)
This think almost looks at the synchronous and fragmentary impacts of Capital Adequacy Proportion (CAR), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Working Costs to Working Salary (BOPO) on the budgetary execution of Indonesian banks, measured by Return on Assets (ROA). Tending to existing holes within the writing, the think about moreover investigates the interaction among these factors and gives overhauled observational prove drawn from assorted bank sorts recorded on the Indonesia Stock Exchange (IDX). Utilizing a quantitative approach with a causal-comparative strategy, information were collected from 10 banks reliably recorded on the IDX over the 2004–2024 period, yielding 210 firm-year perceptions. Auxiliary information were gotten from yearly reports and analyzed utilizing different straight relapse by means of SPSS computer program, taking after classical presumption tests for legitimacy. The comes about appear that CAR, NPL, LDR, and BOPO collectively have a noteworthy affect on ROA. In part, NPL and BOPO contrarily and altogether influence ROA, showing that higher credit chance and operational wastefulness decrease bank benefit. In contrast, CAR and LDR don't appear critical person impacts on ROA. These discoveries propose that whereas administrative compliance and liquidity administration are imperative, they don't straightforwardly improve benefit unless bolstered by viable operational and credit hazard procedures. This study contributes to both academic discourse and banking practice by emphasizing the need for sound risk management and cost control to improve financial performance in the Indonesian banking sector.